2015
DOI: 10.2119/molmed.2015.00220
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Microsatellite Instability, KRAS, BRAF and PIK3CA Mutations in Stage II Colon Cancer Patients

Abstract: In the era of personalized cancer medicine, identifying mutations within patient tumors plays an important role in defining highrisk stage II colon cancer patients. The prognostic role of BRAF V600E mutation, microsatellite instability (MSI) status, KRAS mutation and PIK3CA mutation in stage II colon cancer patients is not settled. We retrospectively analyzed 186 patients with stage II colon cancer who underwent an oncological resection but were not treated with adjuvant chemotherapy. KRAS mutations, PIK3CA mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
0
18
0
1
Order By: Relevance
“…This contradictory finding obviously warrants explanation based on the background of existing literature from the past couple of decades. Vogelaar et al also confirmed a trend toward poorer prognosis in patients with mutant KRAS or BRAF (12). The negative impact of these mutations has been noted by others in both early-and late-stage colorectal cancer (CRC) (11,(14)(15)(16).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…This contradictory finding obviously warrants explanation based on the background of existing literature from the past couple of decades. Vogelaar et al also confirmed a trend toward poorer prognosis in patients with mutant KRAS or BRAF (12). The negative impact of these mutations has been noted by others in both early-and late-stage colorectal cancer (CRC) (11,(14)(15)(16).…”
Section: Resultsmentioning
confidence: 74%
“…In a recent study, in this journal (12), the role of MSI, KRAS, BRAF and PIK3CA in stage II colon cancers was investigated. In the study by Vogelaar et al (12), MSI was found in 23% of patients with a trend toward reduced disease-free and overall survival for patients with MSI, which is in contrast to the prognostic role of MSI found by others in early-stage colon cancers (13).…”
Section: Resultsmentioning
confidence: 99%
“…Sample sizes of the selected studies ranged from 32 to 2693 (median, 266). Among these studies, 21 studies were conducted in Europe, 12 studies in Asia, 6 studies in America, 3 studies in Australia, and the remaining 9 studies were multicenter studies . Twenty‐seven studies were specifically restricted to patients with colon cancer, while other 24 studies investigated patients with colorectal cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Sample sizes of the selected studies ranged from 32 to 2693 (median, 266). Among these studies, 21 studies were conducted in Europe, 6,17,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] 12 studies in Asia, [49][50][51][52][53][54][55][56][57][58][59][60] 6 studies in America, 16,[61][62][63][64][65] 3 studies in Australia, [66][67][68] and the remaining 9 studies were multicenter studies. [69][70][71][72][73][74][75][76]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…La mutación del gen KRAS se comporta como un factor pronóstico negativo para la supervivencia global en el cáncer rectal y para la supervivencia libre de enfermedad en el cáncer de colon en estadio clínico II [87][88][89] ; de la misma manera, la mutación en el BRAF tiene un efecto pronóstico negativo en la supervivencia global en el estadio clínico II 90,91 . Las mutaciones en los genes KRAS y BRAF se asocian significativamente con la supervivencia libre de enfermedad y la supervivencia global más corta en pacientes con tumores de microsatélites estables, pero no en pacientes con tumores con inestabilidad de microsatélites 92 .…”
Section: Utilidad De La Valoración Del Estado De Los Genes En La Prácunclassified